Rozwiązanie:
[tex]a)[/tex]
[tex]f(x)=x^{2}-3x[/tex]
[tex]f'(x)=2x-3[/tex]
[tex]f'(2)=2 \cdot 2 -3 =1[/tex]
[tex]b)\\[/tex]
[tex]f(x)=x^{-3}+x[/tex]
[tex]f'(x)=-3x^{-2}+1[/tex]
[tex]f'(-1)=-3 \cdot 1 +1=-2[/tex]
[tex]c)[/tex]
[tex]$f(x)=\frac{x^{3}}{3-x}[/tex]
[tex]$f'(x)=\frac{3x^{2}(3-x)+x^{3}}{(3-x)^{2}}[/tex]
[tex]$f'(1)=\frac{3(3-1)+1}{(3-1)^{2}} =\frac{3 \cdot 2+1}{4} =\frac{7}{4}[/tex]
[tex]d)[/tex]
[tex]$f(x)=\frac{x-1}{4x+2}[/tex]
[tex]$f'(x)=\frac{4x+2-4x+4}{(4x+2)^{2}} =\frac{6}{(4x+2)^{2}}[/tex]
[tex]$f'(0)=\frac{6}{2^{2}} =\frac{3}{2}[/tex]